2003
DOI: 10.1345/aph.1c325
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin-Induced Clostridium Difficile Diarrhea

Abstract: Mirtazapine in suicidal Huntington's disease TO THE EDITOR: Huntington's disease (HD) is a progressive neurodegenerative disorder, whose major progressive clinical features are chorea, dementia, and psychiatric disturbances such as depression or psychotic episodes. Depression is said to be frequent in HD, and, in various studies, prevalence has varied from 9% to 44%. 1 We report the case of a woman whose severe depression and suicidal ideations secondary to HD were successfully treated with mirtazapine. Case R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…What was unexpected was the relatively high rate of association of CDAD with the fluoroquinolones, particularly levofloxacin and a relatively newer penicillinase-resistant penicillin, piperacillin/tazobactam. Although rarely shown to be associated with C. difficile infection, both fluoroquinolones and piperacillin/tazobactam have been suggested as being potential risk factors in past case reports [8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…What was unexpected was the relatively high rate of association of CDAD with the fluoroquinolones, particularly levofloxacin and a relatively newer penicillinase-resistant penicillin, piperacillin/tazobactam. Although rarely shown to be associated with C. difficile infection, both fluoroquinolones and piperacillin/tazobactam have been suggested as being potential risk factors in past case reports [8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…22-16.74) was highest compared to levofloxacin (AHR 2.52 95% CI 1.68-3.79) and ciprofloxacin (AHR 3.74 95% CI 2.81-4.97). The conclusions from these studies 20,21 in dependently demonstrated a strong association between the newer classes of quinolones (levofloxacin 20,22 gatiflox acin 23 and moxifloxacin 9,24 ) and CDAD. Similarly, in a case-control study done in a Veterans Administration hospital, 30 patients with CDAD were identified over a 6 month period.…”
Section: Difficile Characteristics and Risk Factors For Cdadmentioning
confidence: 83%
“…Various studies have sought to identify the precise strain of C. difficile responsible for the CDAD epidemic. Recently, two major studies have identified a more virulent strain of C. difficile, referred to most commonly as either the BI or NAP1 strain 8,9 which has a 15-20 times enhanced capacity to produce toxins. The strain is characterized in various ways and is referred to as toxin type 3, North American pulsed-field gel electrophoresis type 1, restriction endonuclease analysis group BI and PCR ribotype 027.…”
Section: Difficile Characteristics and Risk Factors For Cdadmentioning
confidence: 99%
“…However, the potential association of fluoroquinolone use with epidemics of C. difficile-associated disease has been the subject of several recent reports [59][60][61][62][63][64]. In the past, C. difficile-associated disease was linked epidemiologically to a variety of antibiotics, including clindamycin, cephalosporins, and ampicillin and ampicillin/sulbactam.…”
Section: Fluoroquinolonesmentioning
confidence: 99%